1992
DOI: 10.1007/bf00245248
|View full text |Cite
|
Sign up to set email alerts
|

2-Hydroxyglutaryl-CoA dehydratase from Fusobacterium nucleatum (subsp. nucleatum): an iron-sulfur flavoprotein

Abstract: Anaerobically prepared cell-free extracts from Fusobacterium nucleatum contain 2-hydroxyglutaryl-CoA dehydratase with a specific activity of 20 nkat mg-1. The enzyme was purified 24-fold to a specific activity of 480 nkat mg-1 by anion exchange chromatography, gel filtration and chromatography on Blue-Sepharose. The activity of the purified enzyme was strictly dependent on the reductant Ti(III)citrate and stimulated 25-fold by 0.15 mM ATP and 5 mM MgCl2. ATP is hydrolysed to ADP during incubation with 2-hydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 32 publications
2
41
0
Order By: Relevance
“…ATP, 5 mM MgCl, and 0.2 mM of the reducing agent Ti(II1)-citrate, as reported for 2-hydroxyacyl-CoA dehydratases (Schweiger et al, 1987;Klees et al, 1992;Hofmeister and Buckel, 1992), was not observed. Moreover the application of 0.2 mM Ti(II1)citrate to the assay led to a 30% decrease in activity.…”
Section: Molecular Properties Of 4-hydroxybutyryl-coa Dehydratasesupporting
confidence: 52%
See 3 more Smart Citations
“…ATP, 5 mM MgCl, and 0.2 mM of the reducing agent Ti(II1)-citrate, as reported for 2-hydroxyacyl-CoA dehydratases (Schweiger et al, 1987;Klees et al, 1992;Hofmeister and Buckel, 1992), was not observed. Moreover the application of 0.2 mM Ti(II1)citrate to the assay led to a 30% decrease in activity.…”
Section: Molecular Properties Of 4-hydroxybutyryl-coa Dehydratasesupporting
confidence: 52%
“…The content of oxidised FAD, iron and labile sulfur led to a new hypothesis for the mechanism of 4-hydroxbutyryl-CoA dehydratase (Fig. 10) analogous to that proposed for lactyl-CoA dehydratase from C. propionicum (Hofmeister and Buckel, 1992) and 2-hydroxyglutarylCoA dehydratase from Fusobacterium nucleatum (Klees et al, 1992). The overall dehydration might proceed in three steps: Firstly, an oxidation of 4-hydroxybutyryl-CoA to 4-hydroxycrotonyl-CoA mediated by the prosthetic group FAD in its oxidised form.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…The dehydratases have to be activated by ATP, Mg 2+ and a reducing agent. In vitro, Ti(III) citrate is applied [11,12,15]; in vivo NADH and probably an additional enzyme serve for this purpose [16]. The activation is catalysed by a polypeptide (HgdC), forming either a third subunit of the dehydratase or an extra separable protein.…”
Section: Dehydration Of 2-hydroxyacyl-coa Estersmentioning
confidence: 99%